GIS-based spatio-temporal assessment of forest cover change and carbon sequestrations of District Abbottabad, Pakistan. Issue 8 (5th August 2022) - Goheer, Muhammad Arif; Hassan, Sher Shah; Gul, Kaenat; Waqar, Mahnoor; Parveen, Nazia
Abstract: Forest plays an important role in the climate of a country and ecosystem's balance. During the last decade, District Abbottabad of Pakistan has gone through extensive land-use changes due to accelerated development, urbanization, and agriculture. This study examines the change in forest cover due to environmental factors with the help of satellite images (Landsat, Sentinel) and their classification through supervised classification, as well as the application of change detection technique after classification using geographical information system (GIS) over the last three decades (1986–2019). The land-use transition matrix was calculated from the year 1986 to 2019. The result shows an overall significant increase of 3.17, 17.24, and 7.24% in the forest, vegetation, and built-up areas, respectively; whereas, water bodies and others (barren land) have decreased significantly by 0.69 and 26.96%, respectively. This study also provides an assessment of the incline of carbon stock from the forest area over the period of the study by 17.19%. HIGHLIGHTS: An increase of 3.17, 17.24, and 7.24% in the forest, vegetation, and build-up areas, respectively. Water bodies and others (barren land) have decreased significantly by 0.69 and 26.96%, respectively. Incline of carbon stock from the forest area over the period of the study by 17.19%. Graphical Abstract